Longevity adjustment of pension benefits - Jukka Lassila (The Research Institute of the Finnish Economy (ETLA), 2007)
In anticipation of future gains in life expectancy, several countries have passed laws that automatically adjust pensions, if life expectancy changes. In this paper we study the effects of longevity adjustment under demographic uncertainty in Finland. If longevity increases, the adjustment decreases the contribution rate, and the reduction is bigger the higher the rate would have been without the reform. On the other hand, longevity adjustment increases the uncertainty in replacement rates. The current middle-aged generations, whose pensions are reduced more than contributions, are likely to experience the largest losses. The full gains are observed far in future. The quantitative results depend on, besides demographic realisations, the specifics of the pension system. Longevity adjustment significantly weakens the defined-benefit nature of the Finnish pension system and brings in a strong defined-contribution flavour. – – How well do the academic resources, company R&D investments and research needs converge to help secure the future competitiveness of the Finnish forest industries?
Keywords: H55; J11; 330; pensions; longevity; demographic uncertainty; Bevölkerungsentwicklung; Sterblichkeit; Alterssicherung; Entscheidung bei Unsicherheit; Finnland